2D Quasi-Geostrophic equation; sub-critical and critical cases. (February 2017) - Dlotko, Tomasz; Sun, Chunyou
Abstract: Our task here is to use a version of the 'vanishing viscosity technique' to study the critical 2D Quasi-Geostrophic equation . The present paper extends and specializes the results reported in Dlotko et al. (2015). We treat now in more detail the solutions of the critical problem ( α = 1 2 ); in particular their uniqueness, regularity and long time behavior.